De mão em mão: o processo criativo de escrita na sala de roteiristas da série original Netflix Boca a boca (2020) - Cavalcante, Raphael Aragão de Carvalho (2023)
The present dissertation seeks to investigate the creative process of writing of the original Brazilian Netflix series Kissing Game (2020) from the analysis of documents of the process, as well as interviews with the screenwriters. In order to do so, the research is based on Genetic Criticism and Process Criticism to examine the creative process from the point of view of documents of process and collaborative work. The research is based on the 'screen idea' (Macdonald, 2004) to observe how the screenplay translates it, and analyzes Douglas (2011), Macdonald (2013), Maras (2009), and Mittel (2015) to study creation, structure, and authorship on the screenplay writing process. The investigation also considers the showrunner function in the process of development to, in the end interpret the process of writing the Bible and the screenplay of the first episode of the show "A gota (step outline)" / "A doença (shooting script)".